2017
DOI: 10.1111/jphp.12683
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal drugs for the treatment of diabetic retinopathy

Abstract: Objectives To explore the various pharmacological actions and the molecular mechanisms behind them by which Chinese herbs tend to lower the risk of developing microvascular diabetic complications in retina and prevent its further progression. Key findings Several Chinese herbs, indeed, elicit potent anti-inflammatory, antioxidant, anti-angiogenic, anti-apoptotic, peroxisome proliferator-activated receptor-gamma receptor agonistic, platelet-activating factor antagonistic, aldose reductase inhibitory and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 73 publications
(144 reference statements)
1
22
0
Order By: Relevance
“…DR is the most common microvascular complication of diabetes mellitus, and one of the leading causes of blindness worldwide [48]. One-third of the worldʼs diabetic population presents different DR stages [88]. DR is a complex event; oxidative stress and inflammation are the main pathways to affect the pathogenesis of DR, which is characterised by neuronal and pericyte cell loss, the formation of acellular occluded capillaries and microaneurysms that result in capillary non-perfusion and hypoxia, increased leukostasis, and vascular basement membrane thickening.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…DR is the most common microvascular complication of diabetes mellitus, and one of the leading causes of blindness worldwide [48]. One-third of the worldʼs diabetic population presents different DR stages [88]. DR is a complex event; oxidative stress and inflammation are the main pathways to affect the pathogenesis of DR, which is characterised by neuronal and pericyte cell loss, the formation of acellular occluded capillaries and microaneurysms that result in capillary non-perfusion and hypoxia, increased leukostasis, and vascular basement membrane thickening.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…GBEs have anti-inflammatory effects, and one of the possible mechanisms is the ability to downregulate the expression of PAF. GBEs can also significantly reduce the transcriptional expressions of hypoxia inducible factor, HIF-1α, and VEGF in retinal pigment epithelial cells under hypoxic conditions [88]. Interleukin regulation appears to play a key role in the anti-inflammatory effect of GBEs [94].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…In a systematic review of African mango for weight reduction, three randomized clinical trials were identified, all of which observed significantly greater weight loss in treated vs. untreated individuals; however, the study quality was poor, precluding recommendation of this supplement for the treatment of obesity [63]. The astragalus root is also found in many non-hCG preparations, and has antioxidant, anti-inflammatory, and PPAR-gamma receptor agonistic properties which may improve insulin sensitivity and glucose homeostasis [64]. Both animal models and in vitro studies have shown that astragalus root is associated with improved measures of metabolic control, including normalized levels of glucose, insulin, and blood lipids.…”
Section: The Hcg Diet: Descriptionmentioning
confidence: 99%
“…LTF can also ameliorate injury due to oxygen free radicals and improve endothelial cell function [13,14]. All herbs in LTF have anti-inflammatory properties and have been found to inhibit inflammation by downregulating nuclear factor-κB (NF-κB) and p38 mitogen-activated protein kinase (p38-MAPK) signaling pathways [15][16][17][18]. However, the anti-inflammatory effects of LTF on DR are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%